Chryseobacterium indologenes in a woman with acute leukemia in Senegal: a case report - Omar, Arouna (BioMed Central, 2014)
INTRODUCTION: This report documents a rare case of Chryseobacterium indologenes urinary tract infection in Senegal. Chryseobacterium indologenes is an uncommon human pathogen reported in hospital outbreaks in Taiwan and there have been some sporadic cases reported in Europe and in the USA mainly from immune-suppressed patients. CASE PRESENTATION: This case report describes a 42-year-old woman of Wolof(a) ethnicity who was hospitalized in our Department of Internal Medicine in a Senegalese university teaching hospital, with acute leukemia who died of severe sepsis 10 days following her hospitalization. A strain of Chryseobacterium indologenes isolated from her urine sample was resistant to several beta-lactams including ampicillin (minimum inhibitory concentrations ≥256μg/mL), cefotaxime (minimum inhibitory concentrations 32μg/mL) and imipenem (minimum inhibitory concentrations ≥32μg/mL), whereas it was susceptible to piperacillin (minimum inhibitory concentrations 16μg/mL), cefepime (minimum inhibitory concentrations 4μg/mL), ceftazidime (minimum inhibitory concentrations 4μg/mL), trimethoprim-sulfamethoxazole (minimum inhibitory concentrations ≤0.25μg/mL) and all tested quinolones including nalidixic acid (minimum inhibitory concentrations ≤2μg/mL). CONCLUSIONS: Chryseobacterium indologenes although uncommon, is an important pathogen causing infection in hospitalized patients. The management of this infection needs better identification, drug susceptibility testing and monitoring of immunosuppressed patients with long hospitalizations.